Preparation method of high-toughness aluminum nitride substrate

Through the composite technology of modified boron nitride nanosheets and AlN whiskers, the problem that aluminum nitride ceramic substrate cannot have both high toughness and high density is solved, and the high-efficiency mechanical properties and thermal conductivity of the ceramic substrate are improved.

CN119569474APending Publication Date: 2025-03-07FUJIAN HUAQING ELECTRONICS MATERIAL TECH

Patent Information

Application Number
CN202411768511.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing aluminum nitride ceramic substrates cannot have both high toughness and high density.

Method used

Modified boron nitride nanosheets and AlN whiskers were used as raw materials, and a high-toughness aluminum nitride substrate was prepared through ultrasonic treatment, ball milling treatment and magnetic stirring.

Benefits of technology

It effectively improves the fracture toughness and mechanical properties of ceramic crystals, while maintaining high density and thermal conductivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of ceramic substrates, provides a preparation method of a high-toughness aluminum nitride substrate, and solves the problem that an aluminum nitride substrate prepared in the prior art cannot have both high toughness and high density. Comprising the following steps: 1) preparing raw materials, namely preparing the following raw materials in parts by weight: 100-110 parts of AlN powder, 6-12 parts of AlN whiskers, 0.1-1 part of modified boron nitride nanosheets, 2-4 parts of a sintering aid, 0.01-0.1 part of polyvinyl alcohol, 1-3 parts of tetraethyl pentamethylene diamine and 1-3 parts of triethyl phosphate; (2) pretreating the modified boron nitride nanosheet; and (3) preparing the high-toughness aluminum nitride substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic substrates, and in particular to a method for preparing a high-toughness aluminum nitride substrate. Background Art

[0002] In recent years, with the continuous development of science and technology, the integrated circuit and other industries have made rapid progress. As the working ability of electronic devices becomes stronger and stronger, the requirements for their internal thermal management are also gradually increasing. This requires that the raw materials should have better thermal conductivity, stability and high toughness. Aluminum nitride ceramic material has 320W·m -1 ·K -1 It has ultra-high theoretical thermal conductivity, excellent mechanical properties, chemical corrosion resistance, and high temperature resistance. Compared with similar ceramic materials, it has high thermal conductivity that Al2O3 does not have, and has incomparable non-toxicity that BeO cannot match. Therefore, it has become the focus of ceramic substrate materials on the current market.

[0003] Chinese patent application No. 202411162234.6 discloses a corrosion-resistant aluminum nitride ceramic substrate and a preparation method thereof. The aluminum nitride ceramic substrate includes the following raw materials in parts by weight: 70 to 90 parts of aluminum nitride powder, 4 to 8 parts of sintering aid, 4 to 16 parts of fluorinated ethylene propylene copolymer, 3 to 7 parts of stearic acid, 4 to 15 parts of ethylene-vinyl acetate copolymer, 1 to 3 parts of dispersant, 2 to 6 parts of plasticizer, and 60 to 70 parts of solvent. Through the above technical solution, the problems of low bending strength and poor corrosion resistance of aluminum nitride ceramic substrates in related technologies are solved. However, the toughness and density of the aluminum nitride ceramic substrate are relatively poor.

[0004] Chinese patent application No. 202410675590.1 discloses a method for preparing aluminum nitride ceramics for chip packaging, comprising the following steps: according to weight, 90-100 parts of aluminum nitride ceramic powder, 5-6 parts of binder, 4-5 parts of sintering aid, 0.6-0.8 parts of leveling agent, 0.05-0.06 parts of rheological aid, 0.2-0.3 parts of defoamer and 40-50 parts of solvent are mixed by wet ball milling, and raw ceramic sheets are prepared by casting and slicing, and sintered after debinding to obtain an aluminum nitride ceramic for chip packaging. In order to prepare aluminum nitride ceramics with high thermal conductivity, the density of the material is improved by adding Al4SiC4 powder treated with sintering aid rare earth metal oxide and binder aminosilane coupling agent; oxygen atoms are avoided from dissolving into the lattice of aluminum nitride as much as possible, so that the prepared aluminum nitride ceramics have the advantages of high thermal conductivity and high flexural strength. However, the toughness of the aluminum nitride ceramic substrate is relatively poor. Summary of the invention

[0005] Therefore, in view of the above problems, the present invention provides a method for preparing a high-toughness aluminum nitride substrate, which solves the problem that the aluminum nitride substrate prepared by the prior art cannot have both high toughness and high density.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a high-toughness aluminum nitride substrate comprises the following steps:

[0008] S1. Preparation of raw materials: including the following raw materials in parts by weight: 100-110 parts by weight of AlN powder, 6-12 parts by weight of AlN whiskers, 0.1-1 parts by weight of modified boron nitride nanosheets, 2-4 parts by weight of sintering aid, 0.01-0.1 parts by weight of polyvinyl alcohol, 1-3 parts by weight of tetraethylpentanediamine, and 1-3 parts by weight of triethyl phosphate;

[0009] S2. Pretreatment of the modified boron nitride nanosheets: adding the modified boron nitride nanosheets to anhydrous ethanol at a solid-liquid ratio of 1:15-20, and ultrasonically treating the modified boron nitride nanosheets for 1-2 hours for later use;

[0010] S3, weighing the AlN powder by weight, adding the pretreated modified boron nitride nanosheets to obtain an AlN mixture, adding anhydrous ethanol to the first mixture in a solid-to-liquid ratio of 1:15-20, mixing evenly, and ball milling for 2-4 hours, adding the sintering aid and the triethyl phosphate by weight, mixing evenly, and ball milling for 2-4 hours to obtain a first slurry;

[0011] S4, weighing the AlN whiskers, adding them to the first slurry obtained in step S3, mixing them evenly, and ball milling them for 0.5-1h to obtain a second slurry;

[0012] S5, adding polyvinyl alcohol and tetraethylpentanediamine by weight to the second slurry obtained in step S4, performing magnetic stirring treatment at a speed of 50-80 r / min for 1-2 hours to obtain a third slurry, then performing a binder removal treatment, and then casting it into a mold, curing for 4-6 hours, demolding and drying, and then pressurizing to 30-35 MPa in a N2 atmosphere, raising the temperature to 1600-1650° C., and keeping the temperature for 2-3 hours to obtain a high-toughness aluminum nitride substrate;

[0013] Wherein, the sintering aid comprises: Y2O3, CaO and Li2CO3, and the molar ratio of Y2O3, CaO and Li2CO3 is 2:2:1;

[0014] The preparation method of the modified boron nitride nanosheets is:

[0015] I. According to the molar ratio of choline chloride to urea of ​​1:2-3.5, the temperature is raised to 80-85° C., and the choline chloride and urea are stirred and mixed uniformly to obtain a first mixed solution;

[0016] II. Take 1-5 parts by weight of hexagonal boron nitride, 50-60 parts by weight of the first mixed solution and 100-120 parts by weight of zirconium oxide balls, mix them evenly, and perform ball milling for 5-6 hours to obtain a fourth slurry;

[0017] III. Wash the fourth slurry obtained in step II in deionized water for 3-5 times, and perform ultrasonic treatment in deionized water to form a suspension. Let the suspension stand for 20-24 hours, collect the supernatant and dry it to obtain modified boron nitride nanosheets.

[0018] Furthermore, the preparation method of the AlN whisker is as follows: according to the molar ratio of Al powder to Si powder of 1:1-3, Al powder and Si powder are mixed and ball-milled for 10-30 minutes, and then transferred to a Si3N4 crucible, and then the Si3N4 crucible is placed in a crystal growth reactor, and the temperature is increased to 1400-1450°C in an Ar atmosphere, and kept warm for 30-60 minutes, and then the temperature is increased to 1700-1750°C in a N2 atmosphere, and kept warm for 2-3 hours, and cooled to room temperature to obtain a crude AlN whisker, and the obtained crude AlN whisker is ultrasonically treated in an anhydrous ethanol solution for 10-20 minutes, centrifuged at a speed of 300-400rpm on a centrifuge for 10-20 minutes, and the supernatant is removed and dried to obtain the AlN whisker.

[0019] Furthermore, the molar ratio of the AlN mixture to the sintering aid is 3:1.

[0020] Furthermore, the particle size of the AlN powder is 0.7-1 μm, and the oxygen content of the AlN powder is ≤0.8 wt %.

[0021] Furthermore, the AlN whisker has a particle size of 0.1-0.6 μm, a length of 5-15 μm, and an oxygen content of ≤2 wt %.

[0022] Furthermore, the debinding treatment is as follows: in a N2 atmosphere of 0.1-0.5 Pa, the heating rate is set to 2°C / min, and the temperature is kept at 950°C for 3 hours.

[0023] Furthermore, the purity of the Al powder and Si powder is ≥99.9%.

[0024] Furthermore, the ultrasonic treatment is carried out in an ultrasonic homogenizer with an ultrasonic power of 300-400W and an ultrasonic time of 30-60min.

[0025] Furthermore, the ball milling process is carried out in a nylon lined vacuum ball mill at a rotation speed of 300-400 r / min, and before ball milling, the vacuum ball mill is evacuated 3-4 times by introducing N2, and the ball-to-material ratio is 2-3:1.

[0026] Furthermore, the drying is carried out under a vacuum environment at a temperature of 80-100° C. for 30-60 minutes.

[0027] By adopting the above technical solution, the beneficial effects of the present invention are:

[0028] 1. Based on the interlayer sliding mechanism, the surface of the AlN ceramic crystal composited with modified boron nitride nanosheets has modified boron nitride nanosheets embedded in the grain boundaries in the holes, and a small amount of modified boron nitride nanosheets will remain at the edges of the edge holes. In the process of pulling out the modified boron nitride nanosheets embedded in the grain boundaries, it is necessary to overcome a large amount of interlayer force, the fracture energy of the molecular bonds in the boron nitride layer, and the friction between the nanosheets and the AlN grains. Therefore, it can effectively improve the fracture toughness of the ceramic crystal, and at the same time effectively improve the mechanical properties of the AlN ceramic without changing its own electrical insulation properties.

[0029] 2. Since embedding boron nitride nanosheets (BNNSs) into AlN grain boundaries will lead to an increase in the number of pores between AlN grain boundaries and grains to a certain extent, the phonon scattering will be strengthened, which will further lead to a decrease in the average degree of freedom of phonons, thereby reducing the thermal conductivity of the product. Therefore, by modifying the boron nitride nanosheets and grafting -OH groups on the surface of BNNSs to form OH-BNNSs, the -OH groups in OH-BNNSs are evenly dispersed in the polyvinyl alcohol (PVA) substrate and can form a hydrogen bond network with the -OH groups on the PVA chain, which can quickly build a thermal conductive path, thereby increasing the thermal conductivity of the product.

[0030] 3. Adding AlN whiskers with a particle size of 0.1-0.6μm and a length of 5-15μm can be well dispersed in the entire system. During sintering, the AlN whiskers break instead of being pulled out, cross-linking with the crack surface of the AlN ceramic crystal and further strengthening through the bridging mechanism, playing a stress role in closing the crack during the crack expansion process, thereby improving the density of the aluminum nitride substrate. DETAILED DESCRIPTION

[0031] Example 1

[0032] A method for preparing a high-toughness aluminum nitride substrate comprises the following steps:

[0033] (1) Preparation of raw materials

[0034] The invention comprises the following raw materials in parts by weight: 100 parts by weight of AlN powder, 6 parts by weight of AlN whiskers, 0.1 parts by weight of modified boron nitride nanosheets, 2 parts by weight of sintering aids, 0.01 parts by weight of polyvinyl alcohol, 1 part by weight of tetraethylpentanediamine, and 1-3 parts by weight of triethyl phosphate;

[0035] (1-1) Preparation of AlN whiskers

[0036] According to the molar ratio of Al powder to Si powder of 1:1, Al powder and Si powder were mixed and ball-milled in a nylon-lined vacuum ball mill for 10 minutes at a rotation speed of 300 r / min. Before ball milling, N2 was introduced into the vacuum ball mill for evacuation 3 times, and the ball-to-material ratio was 2:1. The mixture was then transferred to a Si3N4 crucible, wherein the purity of the Al powder and Si powder was ≥99.9%. The Si3N4 crucible was then placed in a crystal growth reactor, and the temperature was raised to 1400°C in an Ar atmosphere, kept warm for 30 minutes, and then raised to 1700°C in an N2 atmosphere. , keeping warm for 2 hours, cooling to room temperature, obtaining crude AlN whiskers, ultrasonically treating the obtained crude AlN whiskers in anhydrous ethanol solution for 10 minutes, the ultrasonic treatment is carried out in an ultrasonic homogenizer, the ultrasonic power is 300W, the ultrasonic time is 30 minutes, centrifuging at 300rpm for 10 minutes on a centrifuge, removing the supernatant and drying under vacuum at a temperature of 80°C for 30 minutes to obtain the AlN whiskers, the AlN whiskers have a particle size of 0.1 μm, a length of 5 μm, and an oxygen content of the AlN whiskers ≤2wt%;

[0037] (1-2) Preparation of modified boron nitride nanosheets

[0038] I. According to the molar ratio of choline chloride to urea of ​​1:2, the temperature is raised to 80° C., and the choline chloride and urea are stirred and mixed uniformly to obtain a first mixed solution;

[0039] II. Take 1 part by weight of hexagonal boron nitride, 50 parts by weight of the first mixed solution and 100 parts by weight of zirconia balls, mix them evenly, and ball-mill them in a nylon-lined vacuum ball mill for 5 hours at a speed of 300 r / min. Before ball milling, the vacuum ball mill is evacuated 3 times by passing N2. The ball-to-material ratio is 2:1 to obtain a fourth slurry;

[0040] III. Wash the fourth slurry obtained in step II in deionized water for 3 times, and perform ultrasonic treatment in deionized water to form a suspension, let the suspension stand for 20 hours, collect the supernatant and dry it in a vacuum environment at a temperature of 80° C. for 30 minutes to obtain modified boron nitride nanosheets;

[0041] Wherein, the sintering aid comprises: Y2O3, CaO and Li2CO3, and the molar ratio of Y2O3, CaO and Li2CO3 is 2:2:1;

[0042] (2) Pretreatment of modified boron nitride nanosheets

[0043] According to the solid-liquid ratio of the modified boron nitride nanosheets to anhydrous ethanol of 1:15, the modified boron nitride nanosheets were added to anhydrous ethanol for ultrasonic treatment for 1 hour, and then set aside;

[0044] (3) Weighing the AlN powder by weight, wherein the particle size of the AlN powder is 0.7 μm, and the oxygen content of the AlN powder is ≤0.8 wt %, adding the pretreated modified boron nitride nanosheets to obtain a mixture, adding anhydrous ethanol to the first mixture in a solid-to-liquid ratio of 1:15, and mixing evenly, ball milling in a nylon-lined vacuum ball mill for 2 h at a speed of 300 r / min, and evacuating the vacuum ball mill three times by passing N2 before ball milling, and the ball-to-material ratio is 2:1, adding the sintering aid and the triethyl phosphate by weight, and the molar ratio of the AlN mixture to the sintering aid is 3:1, mixing evenly, and ball milling in a nylon-lined vacuum ball mill for 2 h at a speed of 300 r / min, and evacuating the vacuum ball mill three times by passing N2 before ball milling, and the ball-to-material ratio is 2:1, to obtain a first slurry;

[0045] (4) Weighing the AlN whiskers, adding them to the first slurry obtained in step (3), mixing them evenly, and ball milling them in a nylon-lined vacuum ball mill for 0.5 h at a speed of 300 r / min. Before ball milling, the vacuum ball mill was evacuated three times by passing N2, and the ball-to-material ratio was 2:1, to obtain a second slurry;

[0046] (5) Add polyvinyl alcohol and tetraethylpentanediamine by weight to the second slurry obtained in step (4), and perform magnetic stirring at a speed of 50 r / min for 1 h to obtain a third slurry. Then, in a N2 atmosphere of 0.1 Pa, set the heating rate to 2°C / min, keep the temperature at 950°C for 3 h, perform debinding treatment, and then cast it into a mold and cure for 4 h. After demolding and drying, pressurize it to 30 MPa in a N2 atmosphere, increase the temperature to 1600°C, and keep the temperature for 2 h to obtain a high-toughness aluminum nitride substrate.

[0047] Example 2

[0048] A method for preparing a high-toughness aluminum nitride substrate comprises the following steps:

[0049] (1) Preparation of raw materials

[0050] The invention comprises the following raw materials in parts by weight: 105 parts by weight of AlN powder, 10 parts by weight of AlN whiskers, 0.5 parts by weight of modified boron nitride nanosheets, 3 parts by weight of sintering aids, 0.05 parts by weight of polyvinyl alcohol, 2 parts by weight of tetraethylpentanediamine, and 2 parts by weight of triethyl phosphate;

[0051] (1-1) Preparation of AlN whiskers

[0052] According to the molar ratio of Al powder to Si powder of 1:2, Al powder and Si powder were mixed and ball-milled in a nylon-lined vacuum ball mill for 20 min at a speed of 350 r / min. Before ball milling, N2 was introduced into the vacuum ball mill for 4 times to evacuate the vacuum ball mill. The ball-to-material ratio was 3:1. The mixture was then transferred to a Si3N4 crucible. The purity of the Al powder and Si powder was ≥99.9%. The Si3N4 crucible was then placed in a crystal growth reactor. The temperature was raised to 1420°C in an Ar atmosphere and kept warm for 45 min. The temperature was then raised to 1720°C in an N2 atmosphere and kept warm for 45 min. The obtained crude AlN whiskers are subjected to ultrasonic treatment in an anhydrous ethanol solution for 15 minutes, the ultrasonic treatment is carried out in an ultrasonic homogenizer, the ultrasonic power is 350W, the ultrasonic time is 45 minutes, and the mixture is centrifuged at 350 rpm for 15 minutes on a centrifuge. After removing the supernatant, the mixture is dried under vacuum at a temperature of 90°C for 45 minutes to obtain the AlN whiskers, wherein the AlN whiskers have a particle size of 0.3 μm and a length of 10 μm, and the oxygen content of the AlN whiskers is ≤2 wt%;

[0053] (1-2) Preparation of modified boron nitride nanosheets

[0054] I. According to the molar ratio of choline chloride to urea of ​​1:3, the temperature is raised to 82° C., and the choline chloride and urea are stirred and mixed uniformly to obtain a first mixed solution;

[0055] II. Take 3 parts by weight of hexagonal boron nitride, 55 parts by weight of the first mixed solution and 110 parts by weight of zirconia balls, mix them evenly, and perform ball milling in a nylon-lined vacuum ball mill for 5.5 hours at a speed of 350 r / min. Before ball milling, the vacuum ball mill is evacuated 4 times by passing N2. The ball-to-material ratio is 3:1 to obtain a fourth slurry;

[0056] III. Wash the fourth slurry obtained in step II in deionized water for 4 times, and perform ultrasonic treatment in deionized water to form a suspension, let the suspension stand for 22 hours, collect the supernatant and dry it in a vacuum environment at a temperature of 90° C. for 45 minutes to obtain modified boron nitride nanosheets;

[0057] Wherein, the sintering aid comprises: Y2O3, CaO and Li2CO3, and the molar ratio of Y2O3, CaO and Li2CO3 is 2:2:1;

[0058] (2) Pretreatment of modified boron nitride nanosheets

[0059] According to the solid-liquid ratio of the modified boron nitride nanosheets to anhydrous ethanol of 1:18, the modified boron nitride nanosheets were added to anhydrous ethanol for ultrasonic treatment for 1.5 hours, and then set aside;

[0060] (3) Weighing the AlN powder by weight, wherein the particle size of the AlN powder is 0.8 μm, and the oxygen content of the AlN powder is ≤0.8 wt %, adding the pretreated modified boron nitride nanosheets to obtain a mixture, adding anhydrous ethanol to the first mixture in a solid-to-liquid ratio of 1:18, and mixing evenly, ball milling in a nylon-lined vacuum ball mill for 3 h at a rotation speed of 350 r / min, and evacuating the vacuum ball mill four times by passing N2 before ball milling, and the ball-to-material ratio is 3:1, adding the sintering aid and the triethyl phosphate by weight, and the molar ratio of the AlN mixture to the sintering aid is 3:1, mixing evenly, and ball milling in a nylon-lined vacuum ball mill for 3 h at a rotation speed of 350 r / min, and evacuating the vacuum ball mill four times by passing N2 before ball milling, and the ball-to-material ratio is 3:1, to obtain a first slurry;

[0061] (4) Weighing the AlN whiskers, adding them to the first slurry obtained in step (3), mixing them evenly, and ball milling them in a nylon-lined vacuum ball mill for 0.8 h at a speed of 350 r / min. Before ball milling, the vacuum ball mill was evacuated 4 times by passing N2, and the ball-to-material ratio was 3:1, to obtain a second slurry;

[0062] (5) Add polyvinyl alcohol and tetraethylpentanediamine by weight to the second slurry obtained in step (4), and perform magnetic stirring at a speed of 60 r / min for 1.5 h to obtain a third slurry. Then, in a N2 atmosphere of 0.3 Pa, set the heating rate to 2°C / min, keep the temperature at 950°C for 3 h, perform debinding treatment, and then cast it into a mold and cure for 5 h. After demolding and drying, pressurize it to 32 MPa in a N2 atmosphere, increase the temperature to 1620°C, and keep the temperature for 2.5 h to obtain a high-toughness aluminum nitride substrate.

[0063] Example 3

[0064] A method for preparing a high-toughness aluminum nitride substrate comprises the following steps:

[0065] (1) Preparation of raw materials

[0066] The invention comprises the following raw materials in parts by weight: 110 parts by weight of AlN powder, 12 parts by weight of AlN whiskers, 1 part by weight of modified boron nitride nanosheets, 4 parts by weight of sintering aids, 0.1 parts by weight of polyvinyl alcohol, 3 parts by weight of tetraethylpentanediamine, and 3 parts by weight of triethyl phosphate;

[0067] (1-1) Preparation of AlN whiskers

[0068] According to the molar ratio of Al powder to Si powder of 1:3, Al powder and Si powder were mixed and ball-milled in a nylon-lined vacuum ball mill for 30 minutes at a rotation speed of 400 r / min. Before ball milling, N2 was introduced into the vacuum ball mill for 4 times to evacuate the vacuum ball mill. The ball-to-material ratio was 3:1, and then the mixture was transferred to a Si3N4 crucible. The purity of the Al powder and Si powder was ≥99.9%. The Si3N4 crucible was then placed in a crystal growth reactor. The temperature was raised to 1450°C in an Ar atmosphere and kept warm for 60 minutes. Then the temperature was raised to 1750°C in an N2 atmosphere. Keeping the mixture warm for 3 hours, cooling to room temperature, obtaining a crude AlN whisker, subjecting the obtained crude AlN whisker to ultrasonic treatment in an anhydrous ethanol solution for 20 minutes, wherein the ultrasonic treatment is performed in an ultrasonic homogenizer, the ultrasonic power is 400 W, the ultrasonic time is 60 minutes, centrifuging at a speed of 400 rpm for 20 minutes on a centrifuge, removing the supernatant, and drying under a vacuum environment at a temperature of 100° C. for 60 minutes to obtain the AlN whisker, wherein the AlN whisker has a particle size of 0.6 μm, a length of 15 μm, and an oxygen content of the AlN whisker of ≤2 wt%;

[0069] (1-2) Preparation of modified boron nitride nanosheets

[0070] I. According to the molar ratio of choline chloride to urea of ​​1:3.5, the temperature is raised to 85° C., and the choline chloride and urea are stirred and mixed uniformly to obtain a first mixed solution;

[0071] II. Take 5 parts by weight of hexagonal boron nitride, 60 parts by weight of the first mixed solution and 120 parts by weight of zirconia balls, mix them evenly, and ball-mill them in a nylon-lined vacuum ball mill for 6 hours at a speed of 400 r / min. Before ball milling, the vacuum ball mill is evacuated 4 times by passing N2. The ball-to-material ratio is 3:1 to obtain a fourth slurry;

[0072] III. Wash the fourth slurry obtained in step II in deionized water for 5 times, and perform ultrasonic treatment in deionized water to form a suspension, let the suspension stand for 24 hours, collect the supernatant and dry it in a vacuum environment at a temperature of 100° C. for 60 minutes to obtain modified boron nitride nanosheets;

[0073] Wherein, the sintering aid comprises: Y2O3, CaO and Li2CO3, and the molar ratio of Y2O3, CaO and Li2CO3 is 2:2:1;

[0074] (2) Pretreatment of modified boron nitride nanosheets

[0075] According to the solid-liquid ratio of the modified boron nitride nanosheets to anhydrous ethanol of 1:20, the modified boron nitride nanosheets are added to anhydrous ethanol for ultrasonic treatment for 2 hours, and then set aside;

[0076] (3) Weighing the AlN powder by weight, wherein the particle size of the AlN powder is 1 μm, and the oxygen content of the AlN powder is ≤0.8 wt %, adding the pretreated modified boron nitride nanosheets to obtain a mixture, adding anhydrous ethanol to the first mixture in a solid-to-liquid ratio of 1:20, and mixing evenly, ball milling in a nylon-lined vacuum ball mill for 4 h at a speed of 400 r / min, and evacuating the vacuum ball mill four times by passing N2 before ball milling, and the ball-to-material ratio is 3:1, adding the sintering aid and the triethyl phosphate by weight, and the molar ratio of the AlN mixture to the sintering aid is 3:1, mixing evenly, and ball milling in a nylon-lined vacuum ball mill for 4 h at a speed of 400 r / min, and evacuating the vacuum ball mill four times by passing N2 before ball milling, and the ball-to-material ratio is 3:1, to obtain a first slurry;

[0077] (4) Weighing the AlN whiskers, adding them to the first slurry obtained in step (3), mixing them evenly, and ball milling them in a nylon-lined vacuum ball mill for 1 h at a speed of 400 r / min. Before ball milling, the vacuum ball mill was evacuated 4 times by passing N2, and the ball-to-material ratio was 3:1, to obtain a second slurry;

[0078] (5) Add polyvinyl alcohol and tetraethylpentanediamine by weight to the second slurry obtained in step (4), and perform magnetic stirring at a speed of 80 r / min for 2 h to obtain a third slurry. Then, in a N2 atmosphere of 0.5 Pa, set the heating rate to 2°C / min, keep the temperature at 950°C for 3 h, perform debinding treatment, and then cast it into a mold and cure for 6 h. After demolding and drying, pressurize it to 35 MPa in a N2 atmosphere, increase the temperature to 1650°C, and keep the temperature for 3 h to obtain a high-toughness aluminum nitride substrate.

[0079] Comparative Example 1

[0080] The difference from Example 1 is that the AlN whiskers and modified boron nitride nanosheets used in the present application are not used as raw materials. Other technical solutions are the same as those in Example 1.

[0081] The test data of the products of Example 1, Example 2, Example 3 and Comparative Example 1 are shown in Table 1.

[0082] Table 1

[0083] Test items Example 1 Example 2 Example 3 Comparative Example 1 Bending strength(MPa) 459.2 449.3 451.7 372.5 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 4.48 4.13 4.24 2.11 Hardness(GPa) 10.18 9.87 9.97 9.14 <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> 71.3 70.6 71.4 176.4 Density(%) 98.9 98.8 98.8 97.6

[0084] It can be seen from Table 1 that the products prepared by this technical solution have a bending strength greater than 449.3 MPa and a fracture toughness greater than 4.13 MPa·m 1 / 2 , and the hardness is greater than 9.87. Compared with Comparative Example 1, it has better bending strength, fracture toughness and hardness, and the thermal conductivity and density are still at a relatively high level.

[0085] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-toughness aluminum nitride substrate, characterized in that: The following steps are involved: S1. Preparation of raw materials: including the following raw materials in parts by weight: 100-110 parts by weight of AlN powder, 6-12 parts by weight of AlN whiskers, 0.1-1 parts by weight of modified boron nitride nanosheets, 2-4 parts by weight of sintering aid, 0.01-0.1 parts by weight of polyvinyl alcohol, 1-3 parts by weight of tetraethylpentanediamine, and 1-3 parts by weight of triethyl phosphate; S2. Pretreatment of the modified boron nitride nanosheets: adding the modified boron nitride nanosheets to anhydrous ethanol at a solid-liquid ratio of 1:15-20, and ultrasonically treating the modified boron nitride nanosheets for 1-2 hours for later use; S3, weighing the AlN powder by weight, adding the pretreated modified boron nitride nanosheets to obtain an AlN mixture, adding anhydrous ethanol to the first mixture in a solid-to-liquid ratio of 1:15-20, mixing evenly, and ball milling for 2-4 hours, adding the sintering aid and the triethyl phosphate by weight, mixing evenly, and ball milling for 2-4 hours to obtain a first slurry; S4, weighing the AlN whiskers, adding them to the first slurry obtained in step S3, mixing them evenly, and ball milling them for 0.5-1h to obtain a second slurry; S5, adding polyvinyl alcohol and tetraethylpentanediamine by weight to the second slurry obtained in step S4, performing magnetic stirring treatment at a speed of 50-80 r / min for 1-2 hours to obtain a third slurry, then performing a binder removal treatment, and then casting it into a mold, curing for 4-6 hours, demolding and drying, and then pressurizing to 30-35 MPa in a N2 atmosphere, raising the temperature to 1600-1650° C., and keeping the temperature for 2-3 hours to obtain a high-toughness aluminum nitride substrate; Wherein, the sintering aid comprises: Y2O3, CaO and Li2CO3, and the molar ratio of Y2O3, CaO and Li2CO3 is 2:2:1; The preparation method of the modified boron nitride nanosheets is: I. According to the molar ratio of choline chloride to urea of ​​1:2-3.5, the temperature is raised to 80-85° C., and the choline chloride and urea are stirred and mixed uniformly to obtain a first mixed solution; II. Take 1-5 parts by weight of hexagonal boron nitride, 50-60 parts by weight of the first mixed solution and 100-120 parts by weight of zirconium oxide balls, mix them evenly, and perform ball milling for 5-6 hours to obtain a fourth slurry; III. Wash the fourth slurry obtained in step II in deionized water for 3-5 times, and perform ultrasonic treatment in deionized water to form a suspension. Let the suspension stand for 20-24 hours, collect the supernatant and dry it to obtain modified boron nitride nanosheets.

2. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The preparation method of the AlN whisker is as follows: according to the molar ratio of Al powder to Si powder of 1:1-3, Al powder and Si powder are mixed and ball-milled for 10-30 minutes, and then transferred to a Si3N4 crucible, and then the Si3N4 crucible is placed in a crystal growth reactor, and the temperature is increased to 1400-1450°C in an Ar atmosphere, and the temperature is kept for 30-60 minutes, and then the temperature is increased to 1700-1750°C in a N2 atmosphere, and the temperature is kept for 2-3 hours, and the AlN whisker is cooled to room temperature to obtain a crude AlN whisker, and the obtained crude AlN whisker is ultrasonically treated in an anhydrous ethanol solution for 10-20 minutes, centrifuged at a speed of 300-400rpm on a centrifuge for 10-20 minutes, and the supernatant is removed and dried to obtain the AlN whisker.

3. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The molar ratio of the AlN mixture to the sintering aid is 3:

1.

4. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The particle size of the AlN powder is 0.7-1 μm, and the oxygen content of the AlN powder is ≤0.8 wt %.

5. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The AlN whisker has a particle size of 0.1-0.6 μm and a length of 5-15 μm, and an oxygen content of the AlN whisker is ≤2 wt %.

6. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The debinding treatment is as follows: in a N2 atmosphere of 0.1-0.5 Pa, the heating rate is set to 2°C / min, and the temperature is kept at 950°C for 3 hours.

7. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The purity of the Al powder and Si powder is ≥99.9%.

8. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The ultrasonic treatment is carried out in an ultrasonic homogenizer with an ultrasonic power of 300-400W and an ultrasonic time of 30-60min.

9. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The ball milling process is as follows: the ball milling is carried out in a nylon lined vacuum ball mill at a rotation speed of 300-400 r / min, and the vacuum ball mill is evacuated 3-4 times by introducing N2 before ball milling, and the ball-to-material ratio is 2-3:

1.

10. The method for preparing a high-toughness aluminum nitride substrate according to claim 1, characterized in that: The drying is carried out under vacuum at a temperature of 80-100° C. for 30-60 minutes.

Citation Information

Patent Citations

  • A method for preparing aluminum nitride ceramic for chip packaging

    CN118271097B

  • A corrosion-resistant aluminum nitride ceramic substrate and preparation method thereof

    CN118684501B

  • Aluminum nitride whisker reinforced aluminum nitride ceramic composite material for electronic packaging and preparation method

    CN105777169A

  • Green method for stripping hexagonal boron nitride nanosheets

    CN111943150A

  • Method for manufacturing high-heat conductivity aluminium nitride ceramics

    CN1130607A

Cited By

  • Preparation method of high-thermal-conductivity aluminum nitride ceramic substrate

    CN119930300A